LEKSIKON DALAM PROSES PERNIKAHAN ADAT BANJAR DI DESA SUNGAI DANAU KALIMANTAN SELATAN - Anzlina, Nur; Suswandi, Irwan (Universitas Muhammadiyah Surabaya, 2024)
The traditional Banjar wedding process is one of the traditions that is still preserved today. This research aims to find out the lexicon contained in the Banjar traditional wedding process in Sungai Danau Village, South Borneo Province, and also to find out the influence of the behavior of the Banjar ethnic community as a linguistic community. The theories used in conducting this research are anthropolinguistic theory from Sapir-Whorf and lexicon theory from Kridalaksana. This type of research is descriptive qualitative. The data collection methods used are simak method and cakap method. The data analysis method used is the padan referensial method. The results obtained are that there are eleven lexicons in Banjar traditional wedding which can be seen in terms of phonetics, morphology and syntax, as well as the cultural behavior that exists in Banjar tribal society which is a factor in the emergence of lexicons in the Banjar traditional marriage process.